2012
DOI: 10.1186/1751-0147-54-16
|View full text |Cite
|
Sign up to set email alerts
|

Post-antibiotic effect of orbifloxacin against Escherichia coli and Pseudomonas aeruginosa isolates from dogs

Abstract: Orbifloxacin is a fluoroquinolone drug used widely in companion animal medicine. In this study, we firstly determined post-antibiotic effects (PAEs) and post-antibiotic sub-minimum inhibitory concentrations (MIC) effects (PA-SMEs) of orbifloxacin for two strains each of Escherichia coli and Pseudomonas aeruginosa from dogs, and these parameters were compared with those of enrofloxacin. At twice the MIC, the PAEs of orbifloxacin ranged from -0.28-0.93 h (mean, 0.29 h) for E. coli and -0.18-1.18 h (mean, 0.37 h)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
5
2
Order By: Relevance
“…Previously, orbifloxacin and enrofloxacin were tested against E. coli or Pseudomonas aeruginosa and the strains with higher MICs contributed to shorter PAE and PA‐SME versus those with lower MICs (Harada et al . ). However, for the eight isolates/strains used in this study, with the same MICs, they exhibited different persisting suppression periods of bacterial growth.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Previously, orbifloxacin and enrofloxacin were tested against E. coli or Pseudomonas aeruginosa and the strains with higher MICs contributed to shorter PAE and PA‐SME versus those with lower MICs (Harada et al . ). However, for the eight isolates/strains used in this study, with the same MICs, they exhibited different persisting suppression periods of bacterial growth.…”
Section: Resultsmentioning
confidence: 97%
“…The PAEs and PA-SMEs have been studied extensively in different antibiotics not only in human medicine but in veterinary medicine (Bozkurt-Guzel and Gerceker 2012; Harada et al 2012). The spectrophotometric technique and classic viable count method were extensively applied in the determination of PAE.…”
Section: Resultsmentioning
confidence: 99%
“…However, in the Harada et al . study, strains with higher MICs of orbifloxacin and enrofloxacin consistently showed shorter PAE and PASME when compared to those with lower MICs [17]. In another study, two strains of Staphylococcus aureus with the same MICs showed different PAE and PASME [20].…”
Section: Discussionmentioning
confidence: 86%
“…PAE and PASME have increasingly become the focus of investigations designed to determine the optimal dosage regimens for antimicrobial agents, and have been employed to evaluate the effect of sub-MIC of antibacterial agents on pathogens [16] , [17] , [18] , [19] . PAE and PASME are dependent on some factors, such as the concentration of the antibiotic, time of antibiotic exposure, and bacterial species [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics that exert PAE allow the use of lower antibiotic concentrations below the MIC for significant periods of time without risk of re-growth and consequently the administration of antibiotics in an intermittent dose (Carbone et al 2001). Postantibiotic sub-inhibitory concentration effect may play a role as well, and this effect was described for fluoroquinolones (Harada et al 2012). Differences in PAEs were also evident between bacterial strains of the same origin.…”
Section: Discussionmentioning
confidence: 98%